DEVELOPMENT OF REAL TIME INTERNET OF THINGS(IOT) BASED FETAL MONITORING - MOHD AZLAN, MOHD AZRUL (IRC, 2019)
This report discusses a new approach to Development of Real Time Internet of Things(IoT) Based Fetal Monitoring using accelerometer and muscle sensor for monitoring and compute fetus kick conditions. Monitoring fetal wellbeing is key in modern obstetrics as it is routinely used as a proxy to fetal movement. However, it is challenging on getting an accurate, non-invasive and long-term monitoring of monitoring fetal movement when it is outside of hospital environment. In the past few years there are a few accelerometer based system have been successfully invented to tackle common issues in ultrasound measurement and enable remote, self-administrated monitoring of fetal movement. By having multiple accelerometer system is the solution for the system. In this report propose a variable-length accelerometer features and then combine accelerometer data with electromyography (EMG). We compare our method system comprising 2 accelerometer sensors with muscle sensor over a dataset including reference the mother manually counting. So far in the market there is no wearable fetal monitoring system that combine these two types of sensor on detecting the movement of fetal. The results of having these two sensors which is accelerometer and muscle sensor is good. Statistical results from the lab testing and field testing of standard deviation and standard error of mean giving a good accuracy.